2021
DOI: 10.3390/metabo11110741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Flavonoids and Transcripts Involved in Their Biosynthesis in Different Organs of Cissus rotundifolia Lam

Abstract: Cissus rotundifolia Lam. is used as a medicinal herb and vegetable. Flavonoids are the major components for the therapeutic effects. However, flavonoids constituents and expression profiles of related genes in C. rotundifolia organs are unknown. Colorimetric assay showed the highest flavonoid concentration in roots compared to the stem and leaf. Widely target-based metabolome analysis allowed tentative identification of 199 compounds in three organs. Flavonols and flavones were the dominant flavonoids subclass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Quercitrin, quercetin, vitexin, orientin, isovitexin, catechin, isoschaftoside and myricetin were previously reported in C. quadrangularis L. stem extract using LC‐QToF analysis [27] . Hesperidin, epigallocatechin, bergenin, epiafzelechin, isohemiphloin, ononin, and kaempferol hexoside were previously described in the metabolomic profile of C. rotundifolia aerial parts [8,28] . Dihydrokaempferol, apigenin and naringenin were isolates of C. trifoliata stem extract [29] .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Quercitrin, quercetin, vitexin, orientin, isovitexin, catechin, isoschaftoside and myricetin were previously reported in C. quadrangularis L. stem extract using LC‐QToF analysis [27] . Hesperidin, epigallocatechin, bergenin, epiafzelechin, isohemiphloin, ononin, and kaempferol hexoside were previously described in the metabolomic profile of C. rotundifolia aerial parts [8,28] . Dihydrokaempferol, apigenin and naringenin were isolates of C. trifoliata stem extract [29] .…”
Section: Resultsmentioning
confidence: 93%
“…[27] Hesperidin, epigallocatechin, bergenin, epiafzelechin, isohemiphloin, ononin, and kaempferol hexoside were previously described in the metabolomic profile of C. rotundifolia aerial parts. [8,28] Dihydrokaempferol, apigenin and naringenin were isolates of C. trifoliata stem extract. [29] The identified phenolic acids were gallic (2), protocatechuic (3), ferulic (6) and coumaric (10) acids.…”
Section: Hplc-esi-ms/ms Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of petal color change was correlated with the concentration of anthocyanin in plants [ 36 ]. Xue [ 37 ] reported that the anthocyanin content increased as the flower color deepened, and the expression of key structural genes was significantly increased in red-flowered strawberry in comparison with white-flowered strawberry.…”
Section: Discussionmentioning
confidence: 99%